2003
DOI: 10.1016/s0042-6822(03)00006-0
|View full text |Cite
|
Sign up to set email alerts
|

A novel porcine gammaherpesvirus

Abstract: A novel porcine gammaherpesvirus was detected in the blood of domestic pigs by PCR. With degenerate-primer PCR and subsequent long-distance PCR approaches a 60-kbp genome stretch was amplified. Sequence analysis revealed the presence of the gammaherpesvirus ORFs 03 to 46 as well as a putative chemokine receptor and a v-bcl-2 gene. The 60-kbp sequence was compared with the corresponding sequence of the porcine lymphotropic herpesvirus 1 (PLHV-1) published recently and the sequence of PLHV-2, which was amplified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
106
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(113 citation statements)
references
References 41 publications
0
106
3
Order By: Relevance
“…We previously reported the detection of PhaHV-1 in samples from three koalas (koalas A-C, Table 1) using a generic panherpes nested PCR targeting a conserved region of the herpesvirus DNA polymerase (DPOL) gene (Chmielewicz et al, 2003). Direct sequencing of the amplified PCR products showed that the DNA sequences were identical in each sample .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported the detection of PhaHV-1 in samples from three koalas (koalas A-C, Table 1) using a generic panherpes nested PCR targeting a conserved region of the herpesvirus DNA polymerase (DPOL) gene (Chmielewicz et al, 2003). Direct sequencing of the amplified PCR products showed that the DNA sequences were identical in each sample .…”
mentioning
confidence: 99%
“…The unknown sequence (designated PhaHV-X) had 60% pairwise nucleotide identity with PhaHV-1 (GENEious software (http://www.geneious.com/)). To obtain additional PhaHV-X sequence, further PCRs were performed using the degenerative primer DFA paired with primers KG1 or IYG (Chmielewicz et al, 2003), or a reverse primer designed using available PhaHV-1 sequence (PhaHV-1.Rev 59TTCACAGAG-TCCGTGTCGCC93). These PCRs used template extracted from all koala samples that were PCR-positive for herpesvirus DNA .…”
mentioning
confidence: 99%
“…The intergenic regions were 95 % identical. In contrast, the intraspecies nucleic acid identity of PLHV-3 was always more than 99?9 % in coding regions and more than 99?0 % in non-coding regions (Chmielewicz et al, 2003a). Furthermore, domestic pigs have only tested positive for PLHV-3 (Chmielewicz et al, 2003a).…”
mentioning
confidence: 99%
“…Nucleic acid-based (Ehlers et al, 1999b;Chmielewicz et al, 2003a) and 178 bp (excluding primer binding sites) were obtained, the length depending upon the herpesvirus species. When novel sequences were detected, specific primer pairs were designed and retested in the suid species of origin.…”
mentioning
confidence: 99%
See 1 more Smart Citation